2019
DOI: 10.3390/brainsci9050108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GLP-1 Receptor Activation on a Pentylenetetrazole—Kindling Rat Model

Abstract: Objectives: To study the possible anti-seizure and neuroprotective effect of glucagon like peptide 1 (GLP1) analogue (liraglutide) in a pentylenetetrazole (PTZ) induced kindled rat model and its underlying mechanisms. Methods: Thirty Sprague Dawley rats were allocated into 3 equal groups; i) Normal group: normal rats received normal saline, ii) PTZ (kindling) group: received PTZ (50 mg/Kg intraperitoneally (i.p.)) every other day for 2 weeks and iii) PTZ + GLP1 group: same as the PTZ group but rats received li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…It has been reported in some research that GLP-1 analogues demonstrate neuroprotective effects in acute and chronic epileptic mouse models. GLP-1 analogs may exert antiepileptic effects through apoptotic pathways in epileptic mouse models (Koshal and Kumar, 2016;Hussein et al, 2019;Wen et al, 2019). Moreover, the mTOR signaling pathway has been shown to be involved in regulating neuronal function, proliferation, apoptosis, and other cellular processes associated with epileptogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported in some research that GLP-1 analogues demonstrate neuroprotective effects in acute and chronic epileptic mouse models. GLP-1 analogs may exert antiepileptic effects through apoptotic pathways in epileptic mouse models (Koshal and Kumar, 2016;Hussein et al, 2019;Wen et al, 2019). Moreover, the mTOR signaling pathway has been shown to be involved in regulating neuronal function, proliferation, apoptosis, and other cellular processes associated with epileptogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The GLP-1 receptor (GLP-1R) is widely expressed in neurons of several brain subregions such as hypothalamus, hippocampus, and cortex (Cork et al, 2015;Yoshino et al, 2015), suggesting the GLP-1 signaling could modulate a variety of neuronal functions (Korol et al, 2015;Prashant et al, 2018). Indeed, it has been reported that GLP-1 analogues exert neuroprotective effects in mouse models of acute and chronic epilepsy (Koshal et al, 2018;Wang et al, 2018;Hussein et al, 2019). Previous studies have shown that different apoptosis signaling pathways including BCL-2 associated X protein (BAX)/B cell lymphoma 2 (BCL-2) proteins are involved in seizure-induced neuronal death (Guo et al, 2017;Rubio et al, 2019), and liraglutide treatment could reduce the expression of an apoptotic marker caspase-3 in the brain of a Pentylenetetrazole (PTZ)-induced kindled rat model (Hussein et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After preconditioning, all experimental animals received an intraperitoneal injection (i.p.) of 20 mg/kg (The dosage was a moderate dosage compared with those reported by other institutions) pentylenetetrazol (PTZ, Sigma, USA) to generate the convulsion model freely dissolved in saline (solution: 20 mg PTZ dissolved in 1 ml saline) ( 11 , 12 ). Extracorporeal electroencephalogram (EEG) electrodes was placed on 16 rats of each group to monitor the seizure (which don't get the additional PTZ).…”
Section: Methodsmentioning
confidence: 99%
“…15 Researchers also reported that the activation of glucagon like peptide 1 receptor (GLP1R) associated with inhibition of oxidative stress and up-regulation of heat shock protein70 (Hsp70) in hippocampus of rats could exert the protective effects against PTZ-stimulated seizures. 16 In addition, increased level of pro-inflammatory mediators such as IL-1β, IL-6, IL-18 and tumor necrosis factor-α (TNF-α) was reported in rats kindled by PTZ. 17 Tanacetum parthenium (TP), named feverfew, is a member from Asteraceae family which grows in different areas of the world such as Iran.…”
Section: Introductionmentioning
confidence: 99%